2023
DOI: 10.3390/agriculture13030635
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Resistance to Stem Rust and Identification of Sr Genes in Russian Spring and Winter Wheat Cultivars in the Volga Region

Abstract: The Volga region is one of the main grain-producing regions of Russia. Wheat stem rust caused by Puccinia graminis f. sp. tritici is among the most destructive fungal diseases of wheat. Recently, its harmfulness has increased in the Volga region. In this regard, an analysis of the resistance and diversity of the Sr genes in the Russian wheat cultivars is necessary. In this work, 126 wheat cultivars (including 23 durum wheat cultivars and 103 bread wheat cultivars) approved for use in the Volga region were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The Sr31 is an effective Ug99 stem rust population. In contrast, Baranova et al (2023) stated that Sr31 gene was not shown resistance to Ug99. In 2014, Sr50 virulence isolate was found in the greenhouse but this gene is still effective against Ug99 and its derivatives.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Sr31 is an effective Ug99 stem rust population. In contrast, Baranova et al (2023) stated that Sr31 gene was not shown resistance to Ug99. In 2014, Sr50 virulence isolate was found in the greenhouse but this gene is still effective against Ug99 and its derivatives.…”
Section: Discussionmentioning
confidence: 95%
“…As reported previous studies, the combination of the Sr25 gene with the Sr6Agi gene were widely preferred in wheat breeding to stem rust. However,Baranova et al (2023) indicated that wheat cultivars carrying only Sr25 gene were susceptible to Pgt. In a study conducted byXu et al (2018) found that two wheat cultivars are likely to carry this gene pedigree information.…”
mentioning
confidence: 99%
“…As previous studies have reported, the combination of the Sr25 gene with the Sr6Agi gene is widely preferred in wheat breeding to stem rust. However, Baranova et al (2023) indicated that wheat varieties carrying only Sr25 were susceptible to Pgt . In a study conducted by Xu et al (2018) , two wheat varieties carried this gene pedigree information.…”
Section: Discussionmentioning
confidence: 99%
“… Abou-Zeid et al (2023) stated that the resistance genes Sr22 , Sr25 , Sr26 , and Sr50 may currently be the most helpful race-specific resistance genes, depending on how they are used in combination. Most previous studies on this subject have been carried out by various researchers who have identified the frequency of different Sr resistance genes in wheat varieties from different countries ( Baranova et al, 2023 ; Kelbin et al, 2022 ; Li et al, 2016 ; Lin et al, 2021 ; Xu et al, 2018 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Отечественные фитопатологи и селекционеры ведут постоянный поиск сортов и линий с высокими иммунологическими и другими селекционно ценными свойствами (Pakholkova et al, 2022;Sibikeev et al, 2022;Baranova et al, 2023). В производстве должны преимущественно возделываться сорта пшеницы с долговременной неспецифической устойчивостью (Kharina, Sheshegova, 2021).…”
Section: материалы и методыunclassified